How does social media marketing affect the brand equity of food industry in Thailand? - Juntipwong, Preeyaporn (2018)
It is undeniable that online platforms have influenced everyone’s daily lives. Social media is a tool that makes communication between people easier. However, social media not only helps in interpersonal communication but also provides a tool for brands to interact with their customers. Nowadays, with every industry facing strong competition, the brand has to seek an element of uniqueness to compete with others and increase brand equity. Social media is likely to be an important strategy for creating a strong brand. Consequently, this study asks “How does social media marketing affect the brand equity of the food industry in Thailand”. The purpose of the study is to examine the food sector in Thailand in the context of the Thai market. This dissertation provides analyses of the correlation between social media marketing (SMM) and brand equity framework, consisting of brand equity, brand awareness, brand association, brand loyalty, and perceived quality. The data for this study was collected from 516 Thai people aged 18 years and older, using an e-questionnaire survey, and then analysed using the Statistical Package for the Social Sciences (SPSS) program to find a correlation between SMM and brand equity. Basically, the results provide beneficial information for planning market strategy in Thailand for food brands. The results indicate that SMM has a positive relationship with brand equity. However, SMM is not the only factor driving the business. Therefore, this study expects to develop and extend the understanding of social media and brand equity as an alternative choice for Multinational Enterprises (MNEs) to do business aboard. It also provides basic information for further research.